TINGKAT KEPUASAN SISWA TATA BUSANA PADA PENYEDIAAN FASILITAS BELAJAR BUSANA BUTIK SEKOLAH MENENGAH KEJURUAN - Triana Novitasari (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2019)
The purpose of this study was to describe the student’s satisfaction toward learning facilities in classrooms, libraries, and laboratories aspects. This research includes quantitative descriptive research. The data collection methods used questionnaire and documentation. The data analysis technique used descriptive analysis through calculation of Mean, Median, Mode and Standard Deviation. This study showed that student’s satisfaction toward learning facilities in quite a category with relative.14%. Student satisfaction in providing boutique fashion learning facilities consists of suitability of expectations, interest in revisiting, and willingness to recommend. Based on data analysis, the suitability of expectations in the category is quite with a relative frequency of 64.29%, interest in returning to the category is sufficient with a relative frequency of 71.43%, and willingness to recommend in sufficient categories with a relative frequency of 60%. Thus, interest in returning to visit is quite dominant in determining student satisfaction in using practical facilities